Internet robots a new robotics niche. - Taylor, K. (IEEE Robotics and automation magazine)
Web robots are a concept that has captured the interest of researchers and developers. Their potential is being investigated at the University of Western Australia, where a six-axis robot has been made teleoperable over the World Wide Web. The site has been active since September 1994 and the robot has also been exhibited at the Australian National Science and Technology Centre in Canberra. Someone considering offering services with this technology will be interested in which groups of people find it attractive, the level of commitment that operators show, and how the robot users behave. These questions are addressed in the article with some demographic data on operators, an analysis of how long they remain interested, and an examination of how long they will wait to access the service. The user interface affects operator behavior, so some interface variations and their effect on operator actions are considered. The opportunities presented, likely application areas, and the potential for generating an income are examined